Antipredator response of Korean clawed salamander (Onychodactylus koreanus) larvae to odors of potential predators (Chinese minnow, Rhynchocypris oxycephalus and Korean freshwater crayfish, Cambaroides similis) - Jiyeon Cheon; Jongsun Kim; Hyerim Kwon; Jiho Park; Daesik Park (Journal of Ecology and Environment)
Background: To identify and avoid predators, amphibians rely on chemical cues. Onychodactylus koreanus undergo two to three years of the larval stage in mountainous streams, where they encounter various predators. We aimed to identify the potential predators of O. koreanus larvae based on their antipredator responses to predator odors. Additionally, we examined whether the response was innate or can be strengthened by predator olfactory learning. Results: In Experiment 1, O. koreanus larvae exhibited a substantial antipredator response to Chinese minnow (Rhynchocypris oxycephalus) odor but not to Korean freshwater crayfish (Cambaroides similis) odor. In Experiment 2, O. koreanus larvae, who did not previously expose to R. oxycephalus odor, demonstrated a substantial antipredator response to it. Experiment 3 indicated that predator olfactory learning of R. oxycephalus did not enhance the antipredator response of the larvae. Conclusions: Rhynchocypris oxycephalus could prey on O. koreanus larvae, whose antipredator response to R. oxycephalus odor is innate and not enhanced by olfactory learning. Further investigation into the olfactory system of this species may provide insights into the life cycle of O. koreanus, uncovering hidden underground breeding sites and unknown breeding periods.